2014
DOI: 10.3389/fpsyg.2014.00520
|View full text |Cite
|
Sign up to set email alerts
|

The roles of scene priming and location priming in object-scene consistency effects

Abstract: Presenting consistent objects in scenes facilitates object recognition as compared to inconsistent objects. Yet the mechanisms by which scenes influence object recognition are still not understood. According to one theory, consistent scenes facilitate visual search for objects at expected places. Here, we investigated two predictions following from this theory: If visual search is responsible for consistency effects, consistency effects could be weaker (1) with better-primed than less-primed object locations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
(64 reference statements)
1
0
0
Order By: Relevance
“…In line with some other prior research (Heise & Ansorge, 2014), our finding of effective peripheral visual-affective cueing contradicted an eye tracking study that found no affective priming effects of peripheral affective cues on implicit emotional processing (Acunzo & Henderson, 2011). Acunzo and Henderson argued that their failure to show these priming effects was due to the small size of their peripheral cues (perhaps failing to activate the peripheral visual pathway).…”
Section: Participants' Eye Movement Behaviorsupporting
confidence: 82%
“…In line with some other prior research (Heise & Ansorge, 2014), our finding of effective peripheral visual-affective cueing contradicted an eye tracking study that found no affective priming effects of peripheral affective cues on implicit emotional processing (Acunzo & Henderson, 2011). Acunzo and Henderson argued that their failure to show these priming effects was due to the small size of their peripheral cues (perhaps failing to activate the peripheral visual pathway).…”
Section: Participants' Eye Movement Behaviorsupporting
confidence: 82%